Flora liquénica, calcícola del litoral de la provincia de Alicante - Egea, José María; Alonso, F. Luis; Moreno Egea, Pedro Pablo (Universidad de Málaga, Servicio de Publicaciones, 1989)
Se aportan los primeros resultados del estudio que, sobre flora liquénica calcícola, se está llevando a cabo en el litoral mediterráneo del sureste español.Se citan 120 táxones recolectados en 14 localidades del litoral alicantino. Entre los hallazgos de mayor interés destacamos: Arthonia oligospora, Caloplaca tenuatula, Collemopsis schaereri, Dirina inmersa, Gonohymenia nigritella, Gonohymenia nummularia, Lempholemma elveloideum, Peltula obscuratula, Porina acrocordioides, Psorotichia frustulosa, Psorotichia ocellata, Thyrea plectospora y Verrucaria limborioides.

The lichen flora of calcareous rock in the coastal area from Alicante (Spain).First results on the research about lichens flora on calcareous rock in mediterranean seashore from southeastern Spain are commented. 120 taxa, collected in 14 localities from the coastal area of Alicante are listed. The most interesting species are those listed in Spanish summary.